ANALISIS INDUSTRI CPO DI INDONESIA PERIODE: 2006-2010 - , HANI ASTILA AGRIYANTIE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to identify the market structure, conduct and performance of the palm oil industry in Indonesia, and to analyze threats to the profitability of the industry. Analysis tool used is the framework SCP (Structure-Conduct-Performance) and Porter's five forces analysis. The data used in this study is primary data and secondary data. Primary data uses questionnaires distributed at several companies as CPO producers, and secondary data used comes from BPS publications, Statistik Industri Menengah dan Besar. The analysis showed that the market structure of CPO industry in Indonesia is a loose oligopoly, with an average of CR4 for 2006-2010 was 27.5% and CR8 was 32.1%. Prices in the Indonesian CPO industry are determined by Bursa Malaysia Derivatives (Malaysia Derivative Exchange / MDX) and the Rotterdam market, and there is no collusion between oligopolists. Performance of the industry has increased from year to year, as indicated by the value of the PCM during 2006-2010 which has a tendency to increase. The average value of the efficiency of the CPO industry during 2006-2010 is 0.41. Based on the analysis of Porter's Five Forces can be concluded that the CPO industry still has potential for good profitability.